FORMAÇÃO DE PROFESSORAS(ES) PARA O ENSINO DE AGROECOLOGIA: Estudos sobre práticas educativas agroecológicas do Centro de Educação do Campo Roseli Nunes – MA - COSTA, Jocenilson Mendes (2025)
The present research aims to a) analyze how the teaching of Agroecology at the Roseli Nunes Rural Education Center can contribute to the construction of educational practices that enhance the development of environmentally sustainable methodologies, with a view to formulating an educational product that strengthens the peasant identity of students. In addition, b) to identify what conceptions the school administrator, the pedagogical coordinator, the teacher of the technical area of agroecology and other teachers who work in the humanities area, at the Roseli Nunes Rural Education Center, in the Cigra Settlement, in Lagoa Grande do Maranhão, have about Agroecology; c) to determine whether the school that is the focus of this research has integrative methodological proposals for teaching Agroecology; d) to investigate how the theme of Agroecology is worked on at CEC Roseli Nunes with the various areas of knowledge of the common core and the technical area of the curriculum; e) to verify whether the State Department of Education, as well as at CEC Roseli Nunes, provides ongoing training for teachers, focusing on the theme of Agroecology; and f) to develop a Guide of Didactic-pedagogical Guidelines with theoretical-methodological aspects on Rural Education and the teaching of Agroecology integrated with the various areas of knowledge, based on the evidence from this research, which may contribute to the pedagogical work of the Roseli Nunes school. The study is organized into five sections. In the first, we present the introduction, which is subdivided with justification, characterization and delimitation of the research problem, the interest in the research, the structure of the research, in addition to presenting the authors that we used as inspiration for our analyses. The second section deals with Rural Education and Teacher Training, with reflections on the history of rural schools; on the legal frameworks and achievements of rural education, the paradigm of rural education versus rural education, the agrarian issue in Brazil and the right to land, on the professionalization and identity of rural teachers, on rural education from the perspective of the Pedagogy of Alternation and the Pedagogy of the Landless Rural Workers' Movement (MST). In the third section, we discuss Agroecology and curricular practices in rural education, curricula and pedagogical practices in rural education with an emphasis on training through Alternation; Rural Education and Agroecology, the contributions of the MST to Rural Education; Agroecology in the curriculum of rural schools and on curricular practices of the Roseli Nunes Rural Education Center. In the fourth section, we present the methodological procedures of the research, the approach and nature of the research, the Cigra Settlement with the history of the community and the Roseli Nunes Rural Education Center, the Roseli Nunes School, the research participants, the instruments used for data composition, photographic records and the strategies used for collecting the research data. In the fifth section, we address the agroecological educational practices at the Roseli Nunes Rural Education Center – MA and the training of teachers for teaching Agroecology, the conceptions of Agroecology of the research participants, the educational policies aimed at rural populations and the particularities of the Roseli Nunes School, the relationship between the Roseli Nunes Rural Education Center and the community, the educational practices and the methodological proposals developed at the School. This is qualitative research where we used semi-structured interviews as data collection instruments and guided tours, conversation circles and photographic records as collection strategies. The theoretical framework supporting all sections of the research is based on the contributions of authors such as: Caporal (2004), Begnami (2005), Tardif (2006), Arroyo (2008), Molina (2008), Altieri (2012), among others, due to their elucidative, well-founded and consolidated approaches to Rural Education, Agroecology, training, teacher identity and educational practices from the perspective of rural schools. In this sense, we understand that the development of the Guide to Didactic-Pedagogical Guidelines in Agroecology is a possibility to contribute to the strengthening of the educational practices of the Roseli Nunes Rural Education Center, in order to help teachers establish a new relationship between teaching and learning, collaborating greatly in overcoming the challenges that inhibit the space for experimentation of the rural school in its specificity, offering not only theoretical content, but also strategies that enhance teaching and encourage the continuous improvement of the school's pedagogical practice. This research indicated that there is consolidated work on Rural Education and Agroecology at the Roseli Nunes Rural Education Center and that the MST contributes significantly to the training process of teachers, given that the movement has in its horizon the perspective aligned with popular education, which considers the reality of the countryside and fosters social transformation, structuring its practices in Education as a social and political right and that it should promote practices based on Agroecology and sustainable development. The research also found that although there is consolidated work on Rural Education and Agroecology at the Roseli Nunes Rural Education Center, some challenges need to be overcome, in relation to aspects contained in specific laws, but not yet implemented as they should be. The precarious infrastructure of the school and accommodation, lack of technological resources and teaching materials adapted to the rural context, such as textbooks, and mainly, regarding investments in establishing a teaching career for rural school teachers.